Journal of Obstetric Gynecologic & Neonatal Nursing July/August 2006 Vol.35 No.4 - Association Of Women's Health Obstetric And Neonatal Nur (Blackwell Publisher, 2006)
JURNAL OBSTETRI GONEKOLOGI & NEONATAL